MODELLING OF AN ARBITRARILY-ORIENTED MOBILE TELEPHONE HANDSET IN THE FINITE-DIFFERENCE TIME-DOMAIN FIELD COMPUTATION METHOD - Excell, P.S. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The implementation of a generic mobile telephone handset model in the Finite Difference Time Domain (FDTD) method for computation of electromagnetic field distributions is described. The handset can be rotated about the principal FDTD axes to achieve any orientation. The 'thin wire' technique is used to model the antenna in a way that ensures that its correct electrical length is maintained despite the 'staircasing' effect of the FDTD grid. Computed predictions from the model agree with near-field measurements on a physical realisation of the handset, and accurate near and far fields are calculated for arbitrary orientations of the handset. It is concluded that this wire rotation technique has broad application to problems involving components that are required to move in relation to fixed structures. [Vol. 11, No. 2 (1996), pp 55-65]